1993
DOI: 10.1002/abio.370130202
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of proteinase synthesis in Lactococcus lactis

Abstract: The synthesis of extracellular serine proteinase of Lactococcus lactis was studied during the growth in a batch and a continuous culture on chemically defined media. In a batch culture the proteinase synthesis started during the exponential phase of growth and the highest proteinase concentrations were found at the end of the exponential and beginning of the stationary phase of growth. During the growth in a lactose-limited chemostat with amino acids as the sole source of nitrogen, the specific rate of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
1
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
2
15
1
2
Order By: Relevance
“…After growth in low-nitrogen media, the AlaT Ϫ DtpT Ϫ mutant exhibited higher levels of ␤-glucuronidase activity than did the wild-type (Table 3), which can be explained by its lower growth rate than that of the wild type (22). A regulatory role of peptides, and in particular of the dipeptide leucylproline, in proteinase production in L. lactis Wg2 has previously been suggested (21). However, in these experiments, proteinase production was found to be inhibited long after the addition of (di)peptides to the culture.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…After growth in low-nitrogen media, the AlaT Ϫ DtpT Ϫ mutant exhibited higher levels of ␤-glucuronidase activity than did the wild-type (Table 3), which can be explained by its lower growth rate than that of the wild type (22). A regulatory role of peptides, and in particular of the dipeptide leucylproline, in proteinase production in L. lactis Wg2 has previously been suggested (21). However, in these experiments, proteinase production was found to be inhibited long after the addition of (di)peptides to the culture.…”
Section: Discussioncontrasting
confidence: 50%
“…A different growth rate dependency has been observed for synthesis of L. lactis Wg2 proteinase, the level of which in continuous cultures with amino acids as the sole nitrogen source was found to be maximal at a dilution rate of 0.23 h Ϫ1 but decreased at higher dilution rates (21).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The structural prtP gene encodes the proteinase precursor, with a size of approximately 200 kDa, that has homology to the subtilisin family of serine proteases (28, 36). The prtM gene encodes a trans-acting maturase, a lipoprotein of 33 kDa, that is required for the activation of the inactive proteinase precursor (9, 37).Until now, a limited number of studies have dealt with the regulation of proteinase production in lactococci (3,7,11,12,20,22). The results of these investigations showed that proteinase production is mainly dependent on medium composition.…”
mentioning
confidence: 99%
“…This mechanism works through the synthesis of specific enzymes as a response to the stimulus of different environments (Murray et al, 2004;Tunail, 2009). In addition, previous studies have shown that a medium can regulate proteinase activity (Exterkate, 1979;Hugenholtz et al, 1984;Laan et al, 1993;Marugg et al, 1995;Meijer et al, 1996;Smid and Konings, 1990). Daeschel et al (1987) indicated that LAB of a vegetable origin have limited or no proteolytic activity and their amino acid degradation ability is lower compared to other microorganisms.…”
Section: Introductionmentioning
confidence: 99%